The double-peaked Type Ic supernova 2019cad: another SN 2005bf-like object - Gutierrez CP; Bersten MC; Orellana M; Pastorello A; Ertini K; Folatelli G; Pignata G; Anderson JP; Smartt S; Sullivan M; Pursiainen M; Inserra C; et al. (OXFORD UNIV PRESS, 2022)
We present the photometric and spectroscopic evolution of supernova (SN) 2019cad during the first similar to 100 d from explosion. Based on the light-curve morphology, we find that SN 2019cad resembles the double-peaked Type Ib/c SN 2005bf and the Type Ic PTF11mnb. Unlike those two objects, SN 2019cad also shows the initial peak in the redder bands. Inspection of the g-band light curve indicates the initial peak is reached in similar to 8 d, while the r-band peak occurred similar to 15 d post-explosion. A second and more prominent peak is reached in all bands at similar to 45 d past explosion, followed by a fast decline from similar to 60 d. During the first 30 d, the spectra of SN 2019cad show the typical features of a Type Ic SN, however, after 40 d, a blue continuum with prominent lines of Si II lambda 6355 and C II lambda 6580 is observed again. Comparing the bolometric light curve to hydrodynamical models, we find that SN 2019cad is consistent with a pre-SN mass of 11 M-circle dot, and an explosion energy of 3.5 x 10(51) erg. The light-curve morphology can be reproduced either by a double-peaked Ni-56 distribution with an external component of 0.041 M-circle dot, and an internal component of 0.3 M-circle dot or a double-peaked Ni-56 distribution plus magnetar model (P similar to 11 ms and B similar to 26 x 10(14) G). If SN 2019cad were to suffer from significant host reddening (which cannot be ruled out), the Ni-56 model would require extreme values, while the magnetar model would still be feasible.